The Determinants of Audit Quality (Empirical Study in Indonesia Stock Exchange) - Nur Khamisah; Asfeni Nurullah; Nilam Kesuma (Owner : Riset dan Jurnal Akuntansi, 2025)
Every company has an obligation to present quality financial reports. One indicator of quality financial statements is that they have been audited by a public accountant to determine the level of fairness of the financial statements compared to accounting standards. The services of a public accountant or external auditor are seen as an independent third party to anticipate conflicts of interest between company management and shareholders. A public accountant must be able to gather as many clients as possible and gain the trust of the wider community, this requires auditors to maintain good audit quality. Audit quality is very important in maintaining trust in the integrity of financial reporting. The higher the quality produced and perceived, the more credible the financial statements, so as to increase the trust of users of financial statements. This study aims to investigate what factors can affect audit quality. The determinant factors tested in this study are Auditor-Client Geographic Proximity, CEO Financial Expertise, Audit Fee and Audit Complexity. The research was conducted on companies listed on the IDX for the 2018-2022 period. This research was conducted on 766 samples of companies listed on the Indonesia Stock Exchange for the 2018-2022 Period. The data is processed using panel data regression. The results of this study found that geographic distance between auditors and clients, CEO financial expertise and audit complexity have a significant influence in producing higher audit quality. Meanwhile, it was also found that the amount of audit fees has no significant effect on the quality of financial statement audits. From the results of this study, it is hoped that companies can pay more attention to the CEO's financial expertise factor when selecting the CEO, selecting auditors if they want to get a higher quality audit.